2019
DOI: 10.1016/j.jid.2018.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Prolyl Hydroxylases Are Bifunctional Growth Regulators in Melanoma

Abstract: Appropriate post-translational processing of collagen requires prolyl hydroxylation, catalyzed by the prolyl 3-(C-P3H) and prolyl 4-(C-P4H) hydroxylases is essential for normal cell function. Here we have investigated the expression, transcriptional regulation and function of the C-P3H and C-P4H families in melanoma. We show that the CP3H family exemplified by Leprel1 and Leprel2 are subject to methylation-dependent transcriptional silencing in primary and metastatic melanoma consistent with a tumour suppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 25 publications
5
29
0
Order By: Relevance
“…Our findings are supportive of previous work that HIF-1α enhances expression of PLOD2 and promotes metastasis in sarcoma 56 . In addition, the family of collagen prolyl 4-hydroxylases (P4HAs) has been found to be overexpressed in multiple cancers, promoting cancer progression and is associated with poor clinical outcomes 57,58 . The inhibition of collagen prolyl 4-hydroxylases has been suggested as a strategy to reduce invasiveness of breast cancer 57 and B-cell lymphoma 59 however it remains an unexplored strategy in OS.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supportive of previous work that HIF-1α enhances expression of PLOD2 and promotes metastasis in sarcoma 56 . In addition, the family of collagen prolyl 4-hydroxylases (P4HAs) has been found to be overexpressed in multiple cancers, promoting cancer progression and is associated with poor clinical outcomes 57,58 . The inhibition of collagen prolyl 4-hydroxylases has been suggested as a strategy to reduce invasiveness of breast cancer 57 and B-cell lymphoma 59 however it remains an unexplored strategy in OS.…”
Section: Discussionmentioning
confidence: 99%
“…Interfering collagen biosynthesis enzymes Collagen genes MiR-129-5p, MiR-29b, MiR-384 [275][276][277] Prolyl 4-hydroxylase Budesonide, catechol, N-oxalylglycine, coumalic acid, ethyl dihydroxybenzoic acid [278][279][280] Heat shock protein 90 1G6-D7, dipalmitoyl-radicicol, 17-DMAG, ganetespib [281][282][283][284] Heat shock protein 47 MiR-29, 1,3-dimethylol-5-FU, AK778, pirfenidone, terutroban [285,286] Matrix metalloproteinases Gallium complex GS2, isoflavonoids, bisphosphonates [287,288] Lysyl oxidases Beta-aminopropionitrile [289] Disturbing cancer cell signaling pathways Snail transcription factors Toosendanin, ponicidin, ferulic acid [290] Hypoxia-inducible factor Tamoxifen, 28-O-propynoylbetulin [291,292] STAT3 signaling pathway VS-4718, stattic, ruxolitinib, S3I-201 [293,294] TGF-β signaling pathway LY2157299 monohydrate, trabedersen, fresolimumab, galunisertib [295,296] NF-κB signaling pathway Honokiol, aspirin, ormeloxifene [297][298][299] AKT signaling pathway Quetiapine, pirfenidone [300] Notch signaling pathway Rovalpituzumab tesirine, taladegib, crenigacestat, MiR-148a [301] Hedgehog signaling pathway Itraconazole, sonidegib, vismodegib [302] RAS signaling pathway Perindopril, losartan [100,303] Tyrosine kinase receptor Bevacizumab, imatinib, ponatinib, dasatinib [304,305] Discoidin domain receptor WRG-28, 7rh, AZD0156 [306][307][308] G protein family receptor AT13148, KD025, Azaindole 1, chelerythrine…”
Section: Effects Of Inhibitors Targeted Sites Of Inhibitors Typical Imentioning
confidence: 99%
“…Further analysis of these genes/pathways may prove a rich resource to uncover novel metastasis biology. We found that two such genes, KDELR3 and P4HA2 (a collagen prolyl 4-hydroxylase involved in ECM remodeling and associated with worse clinical outcome in melanoma patients 65 ), from our 4-gene functional validation screen are tightly co-expressed in four independent mouse models and in human melanoma patients. This raises the possibility that expression of some genes within our MetDev cohort may be coordinated and/or networked to realize the complex and dynamic phenotypes exhibited by melanocytic cells during development and metastasis.…”
Section: Discussionmentioning
confidence: 88%